Pantang Larang Bermain Waktu Magrib (Kajian Living Hadis Tradisi Masyarakat Melayu Sambas) - Syamsul Kurniawan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Frank Swettenham (2003) assumed Malays as followers of the Prophet Muhammad and believe in fate, but also believe in superstition. As abstinence forbidding children play at sunset, the base develops as a form of their belief in the existence of ghosts and demons. Abstinence for children playing at Magrib is a living hadith phenomenon because it relies on a hadith of the Prophet Muhammad: